Figure 2 from: Han Y-D, Mironov SV, Min G-S (2022) Two new species of feather mites (Acariformes, Astigmata) from the black-tailed godwit, Limosa limosa (Charadriiformes, Scolopacidae), in Korea. ZooKeys 1088: 81-97. https://doi.org/10.3897/zookeys.1088.80307 - Han, Yeong-Deok; Mironov, Sergey V.; Min, Gi-Sik (Zenodo, 2022)
Figure 2 Alloptes (Conuralloptes) neolimosae sp. nov., female A dorsal view B ventral view.